2015
DOI: 10.1161/jaha.114.001584
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Echocardiography and 2D‐3D Speckle‐Tracking Imaging in Chronic Pulmonary Hypertension: Diagnostic Accuracy in Detecting Hemodynamic Signs of Right Ventricular (RV) Failure

Abstract: BackgroundOur aim was to compare three‐dimensional (3D) and 2D and 3D speckle‐tracking (2D‐STE, 3D‐STE) echocardiographic parameters with conventional right ventricular (RV) indexes in patients with chronic pulmonary hypertension (PH), and investigate whether these techniques could result in better correlation with hemodynamic variables indicative of heart failure.Methods and ResultsSeventy‐three adult patients (mean age, 53±13 years; 44% male) with chronic PH of different etiologies were studied by echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 45 publications
4
119
3
4
Order By: Relevance
“…The possibility of RV failure diagnosis in 3D echocardiography and 2D-3D speckle-tracking imaging has been reported by Vitarelli et al (17). In addition, Stergiopoulos et al have shown that speckle-tracking echocardiography (STE) is a sensitive tool for RV dysfunction assessment in acute pulmonary embolism patients (18).…”
Section: Discussionmentioning
confidence: 94%
“…The possibility of RV failure diagnosis in 3D echocardiography and 2D-3D speckle-tracking imaging has been reported by Vitarelli et al (17). In addition, Stergiopoulos et al have shown that speckle-tracking echocardiography (STE) is a sensitive tool for RV dysfunction assessment in acute pulmonary embolism patients (18).…”
Section: Discussionmentioning
confidence: 94%
“…Significant improvement of RVFAC after LVAD implantation may attenuate the association between RVFAC and residual TR. Furthermore, RVFAC emerged as a poor parameter for the determination of RV contractility in recent studies,29, 30 suggesting that, in the presence of TR, estimates of radial contraction may misdiagnose the presence of RV dysfunction because of the decrease in RV afterload caused by the leaking valve, just as the LVEF assessment is limited by MR 13. Tricuspid annular plane systolic excursion, RV index of myocardial performance and/or assessment using 3‐dimensional echocardiography may provide additional information of RV contractility and its association with residual TR 30, 31.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RV size and geometry are technically difficult to determine accurately with 2‐dimensional echocardiography because of its anatomic complexity. Although the 3‐dimensional echocardiography now offers an accurate and real‐time assessment of the size and shape of RV and the TV deformation,30, 36 high feasibility, and reproducibility of TV annulus diameter using 2‐dimensional echocardiography in apical 4‐chamber view has been reported when compared with 3‐dimensional echocardiography 26…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although standard 2D transthoracic echocardiography has provided merely 3 potential treatment goals-preserved tricuspid annulus systolic excursion, normal right atrial area, and the absence of pericardial effusion-modern right heart echocardiography has potentially more to offer. [10][11][12][13][14][15][16][17][18][19][20] Of note, in their study, Ryo et al did not follow this direction but limited the assessment to rather rudimental estimation of RV volumes, simply expecting better precision of the measurements assisted by 3D wall motion tracking when compared with traditional 2D echocardiography. Similar to CMR, this still required manual tracing of endocardial and epicardial borders.…”
Section: See Article By Ryo Et Almentioning
confidence: 95%